PENGARUH PASSION TERHADAP LITERASI MANAJEMEN KEUANGAN - Pristin Prima Sari; Sri Hermuningsih; Anissa Dewi Rahmawati (Universitas Veteran Bangun Nusantara, 2021)
AbstractThe best practice of learning supported by passion that means student interested in specific skill. Passion supported to use ability and knowledge to best achievement. The higher passion thus the higher achievement in outcome and learning. The study aims to empirical evidence the passion of college student to the literacy of financial management for student in management department of Sarjanawiyata Tamansiswa University and to find empirical evidence the improvement of literacy and interest of economic student in financial management. The methodology of research uses quesionairre with online platform the names is Quiziz, moreover statistic tools uses SPSS IBM 20. The beneficial Research such as for developing a learning achievement of college student in financial management, for developing financial management learning learning, and supporting college student to increase interest in financial management. Keywords : Financial Management, Literacy, Passion